How to unmask septal local abnormal ventricular activities with the new LUMIPOINTTM software. Issue 3 (1st May 2020) - Solimene, Francesco; Maddaluno, Francesco; Malacrida, Maurizio; Stabile, Giuseppe
Abstract: We report the use of the new automated tool Lumipoint TM for the detection of LAVA (local abnormal ventricular activities) when they are buried within the far‐field ventricular signal, especially in regions of preserved myocardial thickness, such as the left ventricular (LV) septum. The LV substrate and the tachycardia circuit during ventricular tachycardias of a 60‐year‐old man with dilated cardiomyopathy were mapped using an ultra‐high‐density mapping system and then the Lumipoint TM, analyzing the EGMs of interest, identified the LAVA in the inferoseptal region. This algorithm may be helpful to quickly target the septal substrate avoiding misleading interpretation. Abstract : The Lumipoint tool allows electrophysiologists to quickly identify and target the septal substrate analyzing thousands of electrograms and illuminating signals of interest on the map.